Cardiac tissue citric acid cycle intermediates in exercised very long‐chain acyl‐CoA dehydrogenase‐deficient mice fed triheptanoin or medium‐chain triglyceride. Issue 6 (4th August 2020) - Gaston, Garen; Gangoiti, Jon A.; Winn, Shelley; Chan, Benjamin; Barshop, Bruce A.; Harding, Cary O.; Gillingham, Melanie B.
Abstract: Anaplerotic odd‐chain fatty acid supplementation has been suggested as an approach to replenish citric acid cycle intermediate (CACi) pools and facilitate adenosine triphosphate (ATP) production in subjects with long‐chain fatty acid oxidation disorders, but the evidence that cellular CACi depletion exists and that repletion occurs following anaplerotic substrate supplementation is limited. We exercised very long‐chain acyl‐CoA dehydrogenase‐deficient (VLCAD−/−) and wild‐type (WT) mice to exhaustion and collected cardiac tissue for measurement of CACi by targeted metabolomics. In a second experimental group, VLCAD−/− and WT mice that had been fed chow prepared with either medium‐chain triglyceride (MCT) oil or triheptanoin for 4 weeks were exercised for 60 minutes. VLCAD−/− mice exhibited lower succinate in cardiac muscle at exhaustion than WT mice suggesting lower CACi in VLCAD−/− with prolonged exercise. In mice fed either MCT or triheptanoin, succinate and malate were greater in VLCAD−/− mice fed triheptanoin compared to VLCAD−/− animals fed MCT but lower than WT mice fed triheptanoin. Long‐chain odd acylcarnitines such as C19 were elevated in VLCAD−/− and WT mice fed triheptanoin suggesting some elongation of the heptanoate, but it is unknown what proportion of heptanoate was oxidized vs elongated. Prolonged exercise was associated with decreased cardiac muscle succinate in VLCAD−/− mice in comparison to WT mice. VLCAD−/− fed triheptanoin had increased succinate compared to VLCAD−/− mice fed MCT but lower than WT mice fed triheptanoin. Cardiac CACi were higher following dietary ingestion of an anaplerotic substrate, triheptanoin, in comparison to MCT. Abstract :